Self-Responsibility Gone Bad: Institutions and the 2008 Financial Crisis. (January 2019) - Campbell, John L.
The rise of self-responsibility as practiced in many public policy areas was part of the more general rise of neoliberalism. A case in point is the corporate social responsibility movement. This led in the world of finance to the 2008 financial crisis thanks to various deregulatory moves beginning in the early 1980s. As such, the crisis was the product of a series of incremental institutional changes that enabled corporate self-responsibility in finance to go terribly wrong. Once the crisis hit, a number of more radical institutional changes were pursued in order to reverse the movement toward self-responsibility. This was an institutional rebalancing. This article offers some ideas about how to think about institutional change in the context of this particular corporate self-responsibility movement. It focuses first on the institutional changes that caused the crisis and then on the institutional changes that followed in an effort to minimize the severity of the crisis and reduce the possibility that another one might happen again. The basic argument is that self-responsibility is not a phenomenon that can be reduced to individual action; it cannot work properly without that action being embedded in an appropriate institutional environment. This is an argument at odds with neoliberal theory.